Partisipasi Perempuan dan Pemuda dalam Pengelolaan Limbah Berbasis Teknologi di Program Pesona Subang - Wazirul Luthfi; Andhar Lutfi; Ashlihul Hayati (Jurnal Syntax Admiration, 2025)
The Pesona Subang program as a solution to the problem of technology-based pineapple leaf waste in Subang Regency using a partiborator machine, is a strategy to realize sustainable development, which of course has an impact on various aspects, such as the environment, economy, and social. Of course, the role of women and youth in the implementation of the Subang Charm Program in Cikadu Village is very important, because it can create a big impact, especially on the environment. Meanwhile, the involvement of women and youth in sustainable development is considered crucial, with the involvement of women and youth as beneficiaries of the Subang Charm Program. The implementation of the Subang Charm Program in Subang Regency, West Java, is a solution for processing pineapple leaf waste which has only been thrown away or burned by pineapple farmers. However, through the Pesona Subang Program, it not only reduces the negative impact on the environment, but also contributes to the improvement of the local community's economy through the processing of waste into valuable products that can be sold in a profitable market for the beneficiaries of the Pesona Subang Program.